Morphological and structural changes in thermally-induced soybean protein isolate xerogels modulated by soybean polysaccharide concentration. (December 2022) - Li, Yangyang; Wang, Shengnan; Zhang, Guangchen; Liu, Xiulin; Liu, He; He, Yutang; Zhu, Danshi
Abstract: In this study, xerogels were prepared from soybean protein isolate (SPI) and soybean soluble polysaccharides (SSPS) by thermal induction, and could be changed from two-dimensional (flat sheet) to three-dimensional (curled sheet) by hydration. The effect of SSPS concentration (0–5% w/v) on the deformation of the xerogels during hydration was investigated. The particle size distribution of SPI dispersion with 3% (w/v) SSPS was uniform and the corresponding gels had the greatest strength at 67.5 °C. FT-IR spectroscopy and low-field NMR demonstrated that the interactions between SPI and SSPS were mainly through hydrogen bonding and electrostatic interactions. The presence of 3% SSPS enhances the content of bound water in xerogels and resulted in a significant improvement in their thermal stability. The denaturation temperature was up to 188.6 °C. However, excessive SSPS content (5% w/v) led to a decrease in the thermal stability of xerogels (decreased by ∼5 °C). During hydration, the xerogels spontaneously curled when exposed to water, because of the difference in wettability between the solid-liquid interface and the gas-liquid interface, and hydrogen bond formation between the xerogel polymeric components and water molecules. This novel strategy was able to create 2D xerogels capable of 3D shape changes triggered by water absorption, thereby demonstrating the potential of proteins as deformable materials in functional foods. Graphical abstract: The effect of SSPS concentrations on the deformation and evolution of xerogel during hydration was investigated. Image 1 Highlights: Xerogels with 3% (w/v) SSPS had the lowest critical gel point. The degree of bending during hydration was optimal for xerogels with 3% (w/v) SSPS. Xerogels with 3% (w/v) SSPS were more rapidly able to generate strong gel networks.